2015
DOI: 10.1126/science.aaa0103
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation and microsolvation of DF after F-atom reactions in polar solvents

Abstract: Deuterium fluoride gets born shivering Modern spectroscopic techniques can analyze collisions between gas phase molecules in exquisite detail, highlighting exactly which vibrations and rotations come into play. However, much chemistry of interest takes place in solution, where it's harder to tease out what happens. Dunning et al. applied infrared spectroscopy to study solution-phase formation of deuterium fluoride (DF) from F atoms, a longstanding test bed of gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 49 publications
4
84
0
Order By: Relevance
“…A recent study of fluorine atom reactions in d-acetonitrile illustrates application of TVA and TEA methods to chemical dynamics in solution. 74 XeF2 dissolved in d-acetonitrile served as a precursor to F atoms, which were liberated by UV excitation using a 267-nm, 50 fs duration laser pulse. TEA spectroscopy of the resulting solution probed the XeF photoproduct via its B -X absorption band in the near UV.…”
Section: Transient Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of fluorine atom reactions in d-acetonitrile illustrates application of TVA and TEA methods to chemical dynamics in solution. 74 XeF2 dissolved in d-acetonitrile served as a precursor to F atoms, which were liberated by UV excitation using a 267-nm, 50 fs duration laser pulse. TEA spectroscopy of the resulting solution probed the XeF photoproduct via its B -X absorption band in the near UV.…”
Section: Transient Absorption Spectroscopymentioning
confidence: 99%
“…62 Direct measurements of HCl and HCN vibrational relaxation rates in chlorinated solvents show exponential time constants as long as a few hundred picoseconds to a few nanoseconds, 67,111 whereas DF vibrationally cools in d-acetonitrile in 3 ps. 74 The rates of these processes depend sensitively on the molecular nature of the solvent, and the strength of coupling of solute and solvent modes. 112 Energy transfer to the solvent bath is accelerated by near-resonance of the solute vibrations and solvent motions.…”
Section: Experimental Data On Solvent Response Timescalesmentioning
confidence: 99%
“…Over the last few years, a handful of experimental and theoretical studies have highlighted solution-phase chemical reactions which give rise to products with observable vibrational excitation beyond that which would be expected at thermal equilibrium. [11][12][13][14][15][16][17][18][19] Alongside these observations, a growing number of studies have shown that the extent of vibrational excitation and its subsequent relaxation dynamics can actually impact reaction outcomes in solvents. [20][21][22] For example, there is good evidence that thermal reactions as well-known as alkene hydroboration have a Markovnikov/AntiMarkovnikov product ratio which is determined by the extent of nascent vibrational excitation in the short lived addition complex.…”
Section: Introductionmentioning
confidence: 99%
“…We observe the build-up of ground-state HCN(0) by TVAS, regardless of whether it forms from CN radical reactions with CH3CN or THF, so these reactions are not distinguished in (8) but the experimental data demonstrate that the reaction with THF dominates. The reactive step is significantly faster than the vibrational relaxation processes, and a reduced model that describes our observations is therefore:…”
Section: Effect Of Adding Methanol On Hcn Formation In Acetonitrile 17mentioning
confidence: 92%
“…3 These interactions occur on ultrafast (femtosecond to picosecond) timescales, but non-equilibrium reaction dynamics reminiscent of the gas-phase can persist if reactive events are fast enough to compete with the response of the surrounding solvent. [4][5][6][7][8] To investigate some of the effects of solvent on the dynamics and pathways of bimolecular reactions, ultraviolet (UV) photolysis of dissolved cyanogen iodide (ICN) has been employed as a source of CN radicals. 4,5 These reactive radicals typically abstract hydrogen atoms from organic molecules as shown by Equation (1), and the reactions with alkanes have been extensively studied in the gas phase.…”
Section: Introductionmentioning
confidence: 99%